2004
DOI: 10.1080/02713680490503697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrostatic pressure gradients and Na2EDTA on permeability of human Schlemm's canal cell monolayers

Abstract: Responses of Schlemm's Canal cells to pressure and calcium chelators in vitro are consistent with a role for calcium sensitive junctions in outflow resistance in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…Ethier and Chan (Ethier and Chan, 2001) found that cationized ferritin perfused into enucleated human eyes acted to decreased outflow facility and was seen accumulating near junctions between inner wall endothelial cells. While Ethier and Chan argue that the decreased outflow facility caused by cationized ferritin was due to pore blocking that was also seen to occur in this study, others (Burke et al, 2004) have interpreted their results as consistent with a significant flow through the junctional complexes.…”
Section: Pores As Possible Fixation Artifacts and The Possible Importsupporting
confidence: 57%
See 1 more Smart Citation
“…Ethier and Chan (Ethier and Chan, 2001) found that cationized ferritin perfused into enucleated human eyes acted to decreased outflow facility and was seen accumulating near junctions between inner wall endothelial cells. While Ethier and Chan argue that the decreased outflow facility caused by cationized ferritin was due to pore blocking that was also seen to occur in this study, others (Burke et al, 2004) have interpreted their results as consistent with a significant flow through the junctional complexes.…”
Section: Pores As Possible Fixation Artifacts and The Possible Importsupporting
confidence: 57%
“…These studies have shown that the permeability to solutes, electrical resistance, and hydraulic conductivity can continue to change one to 2 weeks post confluence in endothelial monolayers. Measurements of hydraulic conductivity should only be made after the junctions become stable (Burke et al, 2004). This is especially a concern for studies using steroids or other agents that directly affect these junctions and thus can influence how long they take to become stable (Underwood et al, 1999).…”
Section: Future Workmentioning
confidence: 99%
“…Concerning the study of glaucoma, EHP has been used to mimic ocular hypertension. Several studies have reported the effect of EHP on cells of the trabecular meshwork [18][19][20] and Schlemm's canal [21] and other cell types [22] . The mechanisms whereby retinal cells sense mechanical pressure have not yet been completely elucidated, yet some possibilities have been considered [for a review, see 23 ].…”
Section: Advantages Of Using In Vitro Models To Study Glaucomamentioning
confidence: 99%
“…71,95,119 Inner wall of Schlemm's Canal Endothelia Different groups have isolated and characterized SCECs trying to asses its role in resistance to drainage, but its exact in vivo behavior still remains unclear. [120][121][122][123] Fluid transport across this monolayer does not resemble the typical flow observed across other blood vascular endothelium. In Schlemm's canal, the basal-to-apical directionality of flow pushes the ECs away from their basement membrane, resembling the flow across the lymphatic endothelium.…”
Section: Lymphatic Endotheliamentioning
confidence: 99%
“…Similar to the way lymphatic capillaries respond to strain or pressure gradients by opening interendothelial clefts via anchoring filaments; the inner wall of Schlemm's canal responds to changes in IOP by reducing complexity of intracellular junctions, and decreasing EC overlap. 9,120 The exact route that the aqueous humor follows to exit the conventional pathway has been, for several years, a matter of debate. Two complementary theories, transcellular and paracellular pathways, have been proposed describing aqueous humor outflow; however, the exact contribution of each one of these pathways still remains uncertain.…”
Section: Lymphatic Endotheliamentioning
confidence: 99%